Why Russia attacked Ukraine: Strategic culture and radicalized narratives. Issue 3 (3rd July 2022) - Götz, Elias; Staun, Jørgen
ABSTRACT: This article explores Russia's attack on Ukraine using the lens of strategic culture. Specifically, two strands in Russian strategic culture are identified. The first is a deep-seated sense of vulnerability, especially vis-à-vis "the West." To counter this perceived threat, Russia's national security establishment has long emphasized the importance of possessing strategic depth and buffer zones. The second strand revolves around a feeling of entitlement to great power status. A central component in Russia's great power vision is the right to have a sphere of influence in its Eurasian neighborhood. The article shows that Kremlin officials perceived Ukraine's drift toward the West as a major threat to both Russia's security interests and its status aspirations. As a result, Russia's rhetorical milieu regarding Ukraine became increasingly radicalized. The article concludes that this provided the discursive and intellectual habitat that enabled Putin to launch a large-scale attack.